"Eu vou ser punido por isso até quando?": a (re)inserção do egresso prisional no mercado de trabalho - Hamra, Isabela Calijuri (2021)
The goal of this thesis is to understand how the field of support services for ex-offenders from the penitentiary is organized in São Paulo, focusing on (re)integration of these individuals in the formal job market. The starting point of this analysis is the performance of two non-profit organizations, targeting their methodology, driven by participant observation, and focusing on the comprehension of subjective aspects through the perspective of ex-offenders that have attended those programs. The initial intention to observe the levels of employment showed to be more complex, reaching a symbolic dimension guided by ideologies connected to the neoliberal thinking. The introjection of myths encompasses ideas of entrepreneurship, self accountability and motivacional thinking, acting in a dimension that modifies the perception that the ex-offenders has of itself. However, this symbolic transformation does not necessarily bring material change. The passage rituals promoted by these NGOs produce multiple identity triggers ranging from criminal to worker, showing the permeability between identities considered opposite. The perception of the ex-offenders about the NGOs is that, although they don´t get a formal job, there is a meaningful change in the image they have about themselves, which can lead to a switch in their behavior. Furthermore, the field of actors that integrate the big network of support services for ex-prisoners from the penitentiary in the city of São Paulo has been presented to be diverse and full of relationships between government and non-government entities. This research sought to analyze the performance of government entities, NGOs, private companies and investors, adding to a total of 12 actors who find themselves in a scenario with an abundance of neoliberal ideas and practices.